An interior point method for WLAV state estimation of power system with UPFCs - Rakpenthai C. (2014)
This paper presents a robust state estimator for power system containing unified power flow controller. The estimation problem is formulated as an optimization problem using weighted least absolute value criteria, with a set of equality and inequality constraints. The interior point optimization method is applied to primal and dual formulation in order to solve this problem. Some details of the algorithm, i.e. initialization, step size selection, are also described. The modified IEEE 14- and 118-bus systems are used to demonstrate the effectiveness of the proposed algorithm. The simulation results indicate that the method yields a good state estimate of the system states for a large scale power system with many UPFCs. © 2009 Elsevier Ltd. All rights reserved.